DIGITAL ETIQUETTE IN THE STRUCTURE OF CORPORATE CULTURE OF THE MODERN ORGANIZATION: PHILOSOPHICAL CULTURAL ASPECT - R. I. Mamina; S. I. Tsareva (Дискурс, 2018)
It is shown that the etiquette space of corporate culture of the modern organization functions in two main dimensions, physical and virtual. Analysis of each of these dimensions and its components from the perspective of the philosophical and cultural approach gives the idea of the role and importance of the etiquette regulation in the conditions of modern corporate business environment in real and digital formats. Digital etiquette is analyzed as a three-dimensional concept, which lies at the intersection of humanitarian and technical and technological knowledge, since, on the one hand, it reflects the essential characteristics of etiquette communication in the digital environment, and on the other hand, it is developing under the conditions of a new semantic Web 3.0. and necessarily reflects its nature and functional characteristics. Digital etiquette as a new type of etiquette regulation in virtual environment is illustrated by an example of one the three directions of its development, specifically the practices of user interaction with gadgets, in which such a phenomenon of Internet addiction as phubbing is investigated.